Association between pesticide and polychlorinated biphenyl exposure during pregnancy and autism spectrum disorder among children: a meta-analysis - Fereshteh Mehri; Saeid Bashirian; Salman khazaei; Ensiyeh Jenabi (The Korean Pediatric Society, 2021)
Background The effect of exposure to environmental factors on autism spectrum disorders (ASD), especially during pregnancy, is unclear. Purpose This meta-analysis investigated the association between exposure to pesticides and polychlorinated biphenyls (PCBs) during pregnancy and ASD risk among children. Methods We searched Scopus, PubMed, Web of Science, and ProQuest for articles published through September 2019. Random-effects models were used to examine the association among studies using pooled odds ratios (ORs) and their 95% confidence intervals (CI). I2 tests were used to measure interstudy heterogeneity. Results The pooled OR indicated a significant association between PCB and pesticide exposure during pregnancy and ASD risk among children (OR, 1.80; 95% CI, 1.26-2.34; and OR, 1.20; 95% CI, 1.02-1.39), respectively. Conclusion Findings of the present study indicate that exposure to pesticides and PCBs during pregnancy may affect the risk of ASD among children.